Cardiovascular Risk Factors and Detection of Atrial Fibrillation in the General Population, Makassar, Indonesia: A cross-sectional analysis from a Car-free day - Sumarni Sumarni; Soekarno Hatta; Iskam Syawal (CV. Global Health Publication, 2025)
Cardiovascular disease (CVD) remains the leading cause of death worldwide, with an increasing prevalence in Indonesia. Understanding cardiovascular risk factors associated with arrhythmias in the general population is crucial for effective prevention. This study aims to analyse the relationship between cardiovascular risk factors and the occurrence of atrial fibrillation among participants of Car-Free Day in Makassar, Indonesia. Methods: This cross-sectional study involved 113 respondents during the Car-Free Day event at Hasanuddin University on December 8, 2024. Data on demographics, cardiovascular risk factors, and clinical profiles, including blood pressure, heart rhythm (measured using mobile ECG_5.33.1.apk), and lipid profile, were collected. Results: Of 113 respondents, 46 met the inclusion criteria. Hypertension had the highest prevalence (23.9%), predominantly in individuals over 40 years old. Tachycardia was more common among younger participants (<40 years) and those with obesity. Conclusions: Age is a significant risk factor for hypertension and other cardiovascular disorders. The high prevalence of hypertension among older adults and tachycardia among younger individuals highlights the need for lifestyle modification and early detection strategies in Makassar.